Identify the level of both academic self-efficacy and academic ambition among middle school students in Rafah governorate - Abu Nada, Khaled Mahmoud (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the level of both academic self-efficacy and academic ambition among middle school students in Rafah governorate who have demolished homes, and to uncover the relationship between academic self-efficacy and the level of academic ambition. Besides, the study wanted to identify the differences in the level of both academic self-efficacy and academic ambition among middle school students attributable to the gender variable. The sample was comprised of (125) male and female students. The study used the descriptive approach and concluded the most important findings as follows: the level of academic ambition of middle students in the governorate of Rafah among those with demolished houses reached (74.7) %), and the percentage of the level of academic self-efficacy among middle school students in Rafah governorate with demolished homes reached (74.6%). In addition, the Pearson correlation coefficient between academic ambition and academic self-efficacy was (0.75), and that there were no statistically significant differences in each of academic ambition, and academic self-efficacy attributable to the gender variable.